CLINICAL PROFILE & KNOWLEDGE OF SCRUB TYPHUS AMONG PATIENTS ATTENDING THE TERTIARY CARE HOSPITAL – AN ANALYTICAL STUDY - Neelima varania; Dr. Ritu Bhatnagar (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction: India is a tropical country with a high burden of febrile zoonotic/infectious illnesses, scrub typhus being such a cause with multiple epidemics reported from different regions of the country. Scrub typhus is the commonest of the rickettsial diseases in India and is difficult to diagnose. Pneumonia and acute respiratory distress syndrome (ARDS) are frequent complications.Objectives:  1. To assess signs and symptoms occurring in scrub typhus among patients attending the hospital. 2. To estimate the knowledge of scrub typhus among patients.Material & methods: The study was conducted by Department of Microbiology at PMCH Udaipur from January 2024 to March 2024 and screened for scrub typhus were selected as the study sample. The sample size was calculated as 227 using the Daniel’s formula. A self-administered semi-structured questionnaire was predesigned and pretested Questionnaire to collect data regarding scrub typhus, which was prepared in English and Hindi for data collection. Statistical packages of social sciences (IBM software, version 27) were used to compare the continuous variables between the two groups. P